Health Technology Assessment (HTA) in Peru: current situation and future challenges - Reyes, Nora (2022)
A health technology (drug, vaccine, medical device, procedure) is submitted to a systematic evaluation procedure, called Health Technology Assessment (HTA). The HTA process involves analyzing the properties, benefits, risks and costs of a technology applied to health care, and issuing evidence-based information, linking research and its findings with decision-making in the field of health. Based on the recommendations obtained as a result of the HTA, decision-makers in the health sector choose to admit or reject the incorporation of new health technologies. In Peru, as in the rest of the world, the health technology assessment process has been implemented for approximately ten years, and there are institutions with experience in preparing reports with the results of the HTA. This article provides a general overview of HTA in the world, with special emphasis on their evolution and development in Peru.